X-Ray Diffraction Technique for Residual Stress Measurement in NiCrMo Alloy Weld Metal - Vladimir Ivanovitch Monine; João da Cruz Payão Filho; Rodrigo Stohler Gonzaga; Elisa Kimus Dias Passos; Joaquim Teixeira de Assis (Advances in Materials Science and Engineering)
In the present work, residual stresses in nickel-based (Ni 625) superalloy weld metal of a 9%Ni steel-welded joint were measured by X-ray diffraction (XRD). This technique presents some difficulties in performing measurements in coarse and preferentially oriented weld metal microstructures. It is proposed a preliminary surface treatment by rotating steel wire brushing to perform the stress analysis through XRD technique possible for this kind of material. Stress measurements with proposed XRD technique showed that the stress state in Ni 625 weld metal on the outside surface of the welded joint is characterised by tensile stresses in the transverse and longitudinal directions, while compressive transverse and tensile longitudinal residual stresses are developed in the root pass region.